ANTIBACTERIAL ACTIVITY OF RAMBAI LEAF EXTRACT (Sonneratia caseolaris) CONCENTRATION 25%, 50%, 75%, AND 100% AGAINST Streptococcus sanguinis - Nurul Fathanah Putri; Didit Aspriyanto; Isyana Erlita (Dentino : Jurnal Kedokteran Gigi, 2023)
Background: Dental plaque is a soft layer formed by collection of bacteria that is firmly attached to the tooth surface which if left unchecked can cause tooth decay, periodontal disease and dental caries. Streptococcus sanguinis is the first bacteria to form colonization in plaque formation. Plaque can be diminished by using chlorhexidine gluconate 0,2% mouthwash, but in long-term use it can cause side effects, so an alternative herbal-based mouthwash that has minimal side effects is needed. Rambai leaf extract can be used as an alternative mouthwash because it contains antibacterial compounds, namely, flavonoids, tannins, phenols, triterpenoids, and steroids.  Purpose: The purpose of this study was to determine the antibacterial activity of rambai leaf extract at concentrations of 25%, 50%, 75% and 100% against Streptococcus sanguinis bacteria. Methods: This study used true experimental research with post-test only with a control group design using rambai leaf extract 25%, 50%, 75%, 100%, chlorhexidine gluconate 0.2%, and aquadest. The study used 6 groups with 4 repetitions with a total of 24 samples. Each group was incubated for 24 hours at 37°C, then the diameter of the inhibition zone was measured using a calliper. Results: The results of the Mann Whitney test showed that there was a significant difference between each treatment group and there was no significant difference between 100% rambai leaf extract and chlorhexidine gluconate 0.2%. The average diameter of the inhibition zone of rambai leaf extract was 25% by 9.75 mm, 50% by 13.37 mm, 75% by 16.12 mm, 100% by 19.5 mm, chlorhexidine gluconate 0.2% by 19.12 mm and aquadest 0 mm. Conclusion: Rambai leaf extract with concentrations of 25%, 50%, 75%, and 100% had antibacterial activity against Streptococcus sanguinis. Keywords :  Antibacterial Activities, chlorhexidine gluconate 0,2%,  rambai leaves extracts, Streptococcus sanguinis